Beyond words sobs, hums, stutters and other vocalizations - Connor, Steven 1955- (Reaktion Books, 2014)
In Beyond Words, Steven Connor seeks to understand spoken human language outside words, a realm that encompasses the sounds we make that bring depth, meaning, and confusion to communication. Plunging into the connotations and uses associated with particular groups of vocal utterances - the guttural, the dental, the fricative, and the sibilant - he reveals the beliefs, the myths, and the responses that surround the growls, stutters, ums, ers, and ahs of everyday language.